Aspek yang Menjadi Faktor Penentu Pengelolaan Keuangan Pribadi Mahasiswa S1 FEBP UNHI - Ni Luh Putu Widiantari; Ni Wayan Alit Erlina Wati; Putu Cita Ayu (UNHI Press, 2026)
Managing money is basically about how someone sees and handles their personal finances overall—from assets and budgeting to the resources they have. Interestingly, when students have high financial literacy, they might be more inclined to live a hedonistic lifestyle. That means living in a way that’s all about chasing pleasure—like going out a lot, indulging in entertainment, enjoying city life, buying things they don’t really need, and seeking attention. This research looks into how financial literacy and a hedonistic lifestyle affect financial management. The study was done at the FEBP UNHI Denpasar. Out of a total population of 965 people, 283 respondents were chosen using accidental sampling (basically whoever happened to be available). The analysis used multiple linear regression and found that financial literacy positively affects financial management, while a hedonistic lifestyle has a negative and significant influence.